(untitled) (Research, Society and Development, 2021)
The coronavirus that causes COVID-19 has triggered a series of problems that affect not only the public health sector but also the economy of several countries affected by the current pandemic. In Brazil, numerous attempts to minimize the effects of the disease were applied and with this, preventive measures against the infection were adopted, from the large urban centers as well as industries and rural production. The aim of the present study was to evaluate the adherence to preventive practices against COVID-19 in the agribusiness scenario of the Araguaia Region in the Southeast of the State of Pará. This study is characterized as exploratory with data collection based on the application of a questionnaire aiming to verify the degree of acceptance and reliability of vaccines offered in the national territory, in the perception of individuals who have activities in agribusiness. Therefore, 50% of respondents still cannot have a definitive answer on the efficacy and safety of the immunizing agent, and 71.9% of respondents showed greater confidence in receiving the immunizing agent since it was approved by the national regulatory bodies. As for the protective mask and the use of alcohol gel, 53.1% and 68.7% respectively used these preventive measures throughout the pandemic. Agribusiness suffers from the consequences of the disease. The data obtained in this study point to a concern about the health and economic calamity generated by COVID-19, bringing relevant information about the profile of individuals working in agribusiness in the region studied and their choices regarding methodologies preventive measures currently offered.